2003
DOI: 10.2337/diacare.26.4.1193
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Retinopathy During Pregnancy in Type 1 Diabetic Women Treated With Insulin Lispro

Abstract: OBJECTIVE -To evaluate the progression of retinopathy during pregnancy and postpartum in (insulin-dependent) women with type 1 diabetes treated with insulin lispro or with regular human insulin. RESEARCH DESIGN AND METHODS-A prospective open study of 69 pregnant women with diabetes was performed. A total of 36 of the women were treated with insulin lispro (lispro group) and 33 were treated with conventional short-acting human insulin (regular insulin group). The retinopathy level was estimated by color fundus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 33 publications
1
40
1
1
Order By: Relevance
“…In clinical studies, compared with HI, IAsp provides superior postprandial glycemic control with less risk of major and nocturnal hypoglycemic episodes and small improvement in A1C (20 -24). Safety and efficacy of the use of insulin analogs during pregnancy has yet to be confirmed in randomized controlled trials, although observational studies have not identified cause for concern (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…In clinical studies, compared with HI, IAsp provides superior postprandial glycemic control with less risk of major and nocturnal hypoglycemic episodes and small improvement in A1C (20 -24). Safety and efficacy of the use of insulin analogs during pregnancy has yet to be confirmed in randomized controlled trials, although observational studies have not identified cause for concern (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…As suggested by these results glycemic control measured by A1c was improved in lispro groups versus regular insulin in multiple studies [22,23,26,29], except for the Garcia-Dominguez et al [30] report showing greater A1c levels in the lispro group, p=0.022 [30].…”
Section: Lispromentioning
confidence: 56%
“…They found lower, but non-significant, rates of maternal hypoglycemia (9 vs. 11 women, p=0.42) throughout pregnancy. A1c levels were significantly lower in the lispro group in T2 and T3, but not in T1 (p=0.022) [23].…”
Section: Lispromentioning
confidence: 92%
See 2 more Smart Citations